Radiological assessment of the Bagh Bhairav temple in Kirtipur, Nepal using in-situ gamma ray spectrometry - Anita Mishra; Raju Khanal (Bibechana, 2025)
In this work the results of an in-situ radiological survey of the Bagh Bhairav complex in Kirtipur, Nepal, using a portable gamma ray spectrometer equipped with a GPS and data logger unit is presented. The study aims to assess external exposure by evaluating and mapping external absorbed dose rates and radionuclide activity concentrations in the area. The measured absorbed dose rate in air ranged from 100.330 nGy/h to 170.506 nGy/h, with a mean value of 128.661 ± 14.637 nGy/h. The activity concentrations of the gamma radionuclides 238U, 232Th and 40K, outdoor annual effective dose and excess lifetime cancer risk were found higher than the world average values. The elevated absorbed dose rate is attributed to the high activity concentrations of gamma radionuclides present in soils, rocks at high altitudes. This study provides baseline radiological data for the Bagh Bhairav area and contributes to the limited radiological data available for Nepal.